Successful gamma knife radiosurgery combined with S-1 in an elderly man with local recurrent pancreatic cancer: A case report. Issue 51 (December 2017) - Wei, Juan; Dong, XiaoFang; Du, FangMing; Tang, Sheng; Wei, HangPing
Abstract: Rationale: Pancreatic cancer is common in people older than 40 years, and the incidence peaks at the age of 70 years and older. Chemoradiotherapy has been generally considered a high-risk procedure in elderly patients with local recurrent pancreatic cancer. Gamma knife stereotactic radiosurgery has the advantage in protecting the surrounding tissues, and providing short-term effects. It has been successfully used in patients with brain metastases.The efficacy of GKSRS in other malignancies has barely been studied.S-1 is one of the key drug against metastatic and local advanced pancreatic cancer. The combination of GKSRS and S-1 in local recurrent pancreatic cancer has hardly been reported. Patient concerns: We present a rare case of a 76-year-old man with pancreatic cancer. He complained of recurrent abdominal pain and chronic pain in the right shoulder for more than 3 years. Diagnoses: After several examinations, the diagnosis was carcinoma of the pancreas. Interventions: A resection of the pancreatic neoplasm was performed on June 21, 2011; he did not receive adjuvant chemotherapy. In April 2014, postoperative recurrence was confirmed in the head of the pancreas. The patient received gamma knife stereotactic radiosurgery (GKSRS) combined with S-1 treatment. Outcomes: The patient showed complete response after 2 months. He has achieved an overall survival of 76 months with a very good performance status. Lessons: GKSRS applied to other malignancies has rarely been reported. S-1 is the key drug for adjuvant chemotherapy in resected pancreatic cancer. There are a few studies on this combination in local recurrent pancreatic cancer. GKSRS combined with S-1 seems to be a good option in improving efficacy and prolonging life in elderly patients with locally recurrent pancreatic cancer.